2021
DOI: 10.1093/mnras/stab662
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity radio study of the non-thermal stellar bow shock EB27

Abstract: We present a deep radio-polarimetric observation of the stellar bow shock EB27 associated to the massive star BD+43○3654. This is the only stellar bow shock confirmed to have non-thermal radio emission. We used the Jansky Very Large Array in S band (2–4 GHz) to test whether this synchrotron emission is polarised. The unprecedented sensitivity achieved allowed us to map even the fainter regions of the bow shock, revealing that the more diffuse emission is steeper and the bow shock brighter than previously repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…At the time of writing, low-frequency bow shock studies have only been slightly more successful, as only two runaway stellar bow shocks have been confidently detected at radio frequencies. The prototype radio bow shock was discovered by Benaglia et al (2010) around BD+43 o 3654 and further observed by Brookes (2016) and Benaglia et al (2021). More recently, MeerKAT observations of the X-ray binary Vela X-1 discovered radio emission from its known bow shock (Van den Eijnden et al 2022).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…At the time of writing, low-frequency bow shock studies have only been slightly more successful, as only two runaway stellar bow shocks have been confidently detected at radio frequencies. The prototype radio bow shock was discovered by Benaglia et al (2010) around BD+43 o 3654 and further observed by Brookes (2016) and Benaglia et al (2021). More recently, MeerKAT observations of the X-ray binary Vela X-1 discovered radio emission from its known bow shock (Van den Eijnden et al 2022).…”
Section: Introductionmentioning
confidence: 94%
“…In this scenario, developed over the past decade by many authors (e.g. Benaglia et al 2010Benaglia et al , 2021 Table 2. Summary of the radio measurements for the bow shocks considered in the calculations in Section 4.…”
Section: Non-thermal/synchrotron Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they are mostly visible in the infrared waveband (van Buren & McCray 1988;van Buren et al 1995;Povich et al 2008;Peri et al 2012Peri et al , 2015Kobulnicky et al 2016Kobulnicky et al , 2017 whose emission are governed by dust physics (Henney & Arthur 2019a,b,c;Henney et al 2019). Stellar wind bow shocks also exhibit polarized emission (Shrestha et al 2018(Shrestha et al , 2021 and they are suspected to be cosmic-ray accelerators (del Valle & Pohl 2018;Benaglia et al 2021). While massive stars run away, stellar evolution keeps going, and, consequently, a significant fraction of all core-collapse supernova remnants involve a runaway progenitor (Eldridge et al 2011).…”
Section: Introductionmentioning
confidence: 99%